Internal Media and External Media in Public Relations - Nadia Zulfa Khoiriyah; Muhammad Rifki Faizal Muzaki; Haifa Zahrotunnisa'; Chusnul Chotimah (Yayasan Adra Karima Hubbi, 2024)
Background. The role of public relations is at the forefront of an agency/organization to optimize and manage all forms of activities to create, build, improve, maintain the image and publish all forms of information to the public, as well as establishing cooperation with both internal and external media and all the public so that it can helps facilitate the process of good public relations work in providing information to the public. Because the public and media are supporting tools that encourage public relations work programs. Purpose. This research aims to analyze how internal media is used by organizations in maintaining effective communication with employees, management and other internal stakeholders. Method. The research method we use in writing this article is a literature review or approach used in research to identify, evaluate and synthesize literature from sources (books, sources and articles). Results. The results of this research show that the role of public relations is to increase the positive image of higher education institutions in the eyes of the public, to establish cooperation with internal and external media, as well as the role of bridging all forms of information, both academic and non-academic. The public relations work program includes all campus events or activities related to departments, faculties, or university level to be made into news that is published to the public using internal and external media. Conclusion. Internal media is media owned by an organization or company that is used by public relations to convey messages to the internal public. External media in public relations are public relations activities directed at audiences outside the Company, such as the public, agents, consumers, government and mass media. The purpose of internal and external public relations media is to communicate information and increase awareness and understanding between internal and external parties of the organization.